Customer's satisfaction toward online banking at Pusat Kemahiran It Base, Parit Raja Batu Pahat / Siti Adawiyah Kamal Ariffin - Kamal Ariffin, Siti Adawiyah (Faculty of Business and Management, 2013)
Pusat Kemahiran IT Base, Parit Raja is considered fortunate for having a comprehensive and complete basic infrastructure and facilities. In term of the composition, Pusat Kemahiran IT Base, Parit Raja is predominantly Malay. At Pusat Kemahiran IT Base, Parit Raja there has 300 students and 22 staffs. As world developing and technology become the priority to do daily routines, the researchers want to identify the acceptance of online banking among staffs and students at Pusat Kemahiran IT Base, Parit Raja. In addition, people who live in town area already familiar with the use of online banking. Most of the banking sector provide online banking to customers because they believe that online banking can attract more customers as well as beneficial to them too. Accord ing to Muniruddeen (2007), the fusion of banking sector has lead to the internet banking as new channel for banks to deliver their service for customers as Online banking nowadays become an option for almost people to do bank ' s matters because they no need to go at the bank in order to access their personel and business account information. Moreover, they can make online payment and check their balance out of office hour. Kent Erikson (2003) claimed that due to the social interaction and fulfillment of need, internet technology is a consumers most preferred. The use of online banking back then never practice and the development of technology has been affects the people nowadays to use it precisely in their daily activities. The traditional banking business has been significantly and automatically impacted by the rapid technological development. This is including the online banking system that has been practice by many banking sectors. It had been seen that the business world remarkably when throw with a great revolution which similarly occurred in newly developed nation like Malaysia. In addition , customer nowadays prefers to do online transaction because it gives many advantages like faster and convenient. Kent Erikson (2003) said consumers choose to use internet banking due to the chaos freedom with the new practices and increase the efficiency of services by bank sector. Currently, governments try to provide internet connection at all citizen. Therefore, they have opport unity to use online banking services without going to the town for only to do banking matters. While bankers should also develop and broaden the online banking services to allow customers do their transaction anywhere. As time goes on, the awareness and acceptance of online banking services will increase from time to time. (Tahir Masood, 2008).